Correlation of organic acid tolerance and genotypic characteristics of Listeria monocytogenes food and clinical isolates. (June 2022) - Myintzaw, Peter; Pennone, Vincenzo; McAuliffe, Olivia; Begley, Máire; Callanan, Michael
Abstract: A collection of Listeria monocytogenes isolates from various food products, food processing environments and clinical sources (n = 153) were evaluated for their tolerance to acetic, lactic and propionic acids. A large variation in tolerance was observed amongst isolates under mildly acidic conditions (pH 5.3) for acetic (5–20 mM undissociated acid) and propionic acid (2–10 mM undissociated acid) but there was less variation for lactic acid (3–6 mM undissociated acid). Analysis of the isolate genome sequences for a complement of genes previously shown to have a role in acid tolerance revealed that thiT, gadT2, gadD2 and gadD3 genes were linked to higher acetic acid tolerance ( P  < 0.05) while lisRK was linked to higher tolerance to propionic acid ( P  = 1 × 10 −11 ). An absence of plasmid genes was also linked with isolates showing higher tolerance for all acids. Scoary GWAS analysis revealed that a total of 333, 207, and 333 genes were associated with acid tolerance for acetic, lactic, and propionic acid, respectively ( P  < 0.05). However, the p-value adjusted with Bonferroni's method for multiple comparisons did not reveal any significant associations. Isolates were grouped into clonal complexes (CC) using Multi Locus Sequence Typing (MLST) and MIC values for the three acids were determined for representative strains. One complex, CC18, showed significantly higher ( P  ≤ 0.05) acetic and propionic acid MIC values than other groups, whereas only CC7 type isolates revealed significantly higher ( P  ≤ 0.001) lactic acid MIC values. The results demonstrate that MLST typing could be linked to acid tolerance phenotypic traits which is important in predicting the behaviour of L. monocytogenes in food products. Highlights: The variation in organic acid tolerance of 153 Listeria monocytogenes isolates was determined. Links between certain genes and organic acid tolerance were identified. Isolates were grouped into clonal complexes (CC) according to core genome MLST typing. Isolates belonging to CC18 showed significantly higher acetic and propionic acid tolerance. CC7 type isolates revealed significantly higher lactic acid tolerance.